Effect of foliar application of zinc on annual productivity, foliar nutrients, bioactive compounds and oxidative metabolism in pecan - Ojeda-Barrios Damaris L.; Cruz-Alvarez Oscar; Sánchez-Chavez Esteban; Ciscomani-Larios Juan P. (Folia Horticulturae, 2023)
Pecan nut production is quite commonly limited by zinc (Zn) deficiency. Here, we evaluate the response in terms of the concentrations of non-structural carbohydrates, yield components, foliar nutrient levels and oxidative metabolism in young ‘Western Schley’ pecan nut trees in response to foliar applications of 200 mg · L−1 of Zn as one of the following: ZnSO4, Zn-EDTA, ZnO nanoparticles (NPs) or the proprietary product ‘nitrazinc’ (NZN) (the control). Across two consecutive growing seasons, the spraying of Zn in these various forms helped maintain the foliar concentrations of non-structural carbohydrates, foliar nutrients (total-N, Ca2+ and Mg2+) and the kernel percentage of nuts. Likewise, trees sprayed with ZnSO4 maintained the concentrations of Zn in the leaflets across seasons. On the other hand, Zn-EDTA decreased the concentration of chlorophyll and total carotenoids. In general, leaflets treated with ZnSO4, Zn-EDTA and ZnO NPs reduced their oxidative metabolism. Sources of Zn – such as ZnSO4 – are commercially viable alternatives suitable for increasing the performance of some parameters associated with the yield and quality of nuts in pecan. It would be worthwhile to determine the optimal Zn dose rates for the various pecan cultivars in common use and also to increase our understanding of the physiological and biochemical changes associated with foliar Zn applications.